Influence of Rimantadine, Ribavirine and Triazavirine on Influenza A Virus Replication in Human Monolayer and Lymphoblastoid Cell Lines - T. D. Smirnova; D. M. Danilenko; M. YU. Eropkin; E. G. Deeva; O. I. Kiselev (Антибиотики и Химиотерапия, 2020)
The influence of antivirals, such as rimantadine, ribavirine and triazavirine on influenza virus replication in human cell cultures was evaluated. All the antivirals inhibited viral nucleoprotein NP synthesis. The strongest effect was shown for ribavirine in lung carcinoma A-549 cells and endothelial ECV-304 cells. Hoechst-33258 staining revealed induction of apoptosis in all the cell lines. Rimantadine and ribavirine inhibited virus-induced apoptosis while ribavirine enhanced it. The effect was registered in monolayer cell cultures as well as in suspension cell cultures. The influence of the antiviral drugs on the virus-induced cell proliferation in the suspension cell cultures is also described.